Further Research on an Anti-Swing Control System for Overhead Cranes - Spruogis, B.; Jakstas, A.; Gican, V.; Turla, V.; Moksin, V. (Engineering, Technology & Applied Science Research, 2018)
A method of reducing load oscillations that occur when overhead crane reaches destination position is presented in the article. The use of control drive scheme of crane bridge and trolley that ensures a smooth phase trajectory transition of the load to the optimum trajectory in accordance with Pontryagin's maximum principle is proposed. Mentioned control system changes the magnitude or direction of the traction force at the moment when the load is located above the destination. It is found that the degree of change of the traction force depends on the hoisting rope deviation angle from vertical. This study was conducted in order to provide more accurate and fast handling of loads by overhead crane.